Comparison of clinical fit of three-unit zirconia fixed prostheses fabricated using chairside and labside CAD/CAM systems - Ahn, Jong-Ju (J Dent Sci, 2020)
The purpose of this study was to assess the clinical fit provided by EZIS system, the newly commercialized chairside CAD/CAM system. Prostheses were fabricated with the chairside CAD/CAM system (CS) and labside CAD/CAM system (LS) and marginal, axial, and occlusal fit of the prostheses were compared and analyzed by using replica technique. CS group presented significantly lower fit in all the three fits compared to LS group. Differences in marginal fit, axial fit, and occlusal fit were 12.57 μm (P < 0.001), 3.32 μm (P < 0.05), and 17.20 μm (P < 0.05), respectively. Newly commercialized EZIS system yielded clinically feasible fit; however, further researches covering its biomechanical, physiological, stability aspects are required to promote active clinical use.